Anterior segment reconstruction with artificial iris and Descemet membrane endothelial keratoplasty: a staged surgical approach. Issue 7 (26th February 2021) - Ang, Marcus; Tan, Donald
Abstract : Purpose: To describe a surgical approach that involves anterior segment reconstruction with CustomFlex Artificial Iris (CAI; HumanOptics, Erlangen, Germany) followed by Descemet membrane endothelial keratoplasty (DMEK) in complex eyes with corneal decompensation. Methods: Restrospective case series of eyes that underwent anterior segment restoration involving (1) synechiolysis of peripheral anterior synechiae and excision of iris remnants, (2) securing a well-fixated posterior chamber intraocular lens and (3) suture-fixated or capsular bag placement of CAI. All eyes then underwent DMEK using a pull-through technique with the DMEK EndoGlide (Network Medical Products, Ripon, UK). Main outcomes were successful anterior segment restoration and corneal clarity with central corneal thickness (CCT). Results: Five eyes of five patients (median age 61 years, range 27–69 years; 60% female) underwent anterior segment reconstruction with CAI implantation (4 suture-fixated), followed by successful DMEK surgery (median 2 months later, range 1–5 months). There were no major intraoperative complications or primary graft failure, with one peripheral graft detachment that underwent a successful re-bubble at 1 week. All eyes had stable CAI implants and DMEK grafts remained clear at last follow-up with reduction in mean central corneal thickness (preoperative: 658±86 µm vs postoperative: 470±33 µm, p=0.005). Conclusion: This pilot study highlights a feasible approach of initial anterior segment reconstruction with CAI implantation, prior to DMEK, in eyes with significant anterior segment abnormalities such as iris damage or extensive peripheral anterior synechiae and corneal decompensation.